1990
DOI: 10.1161/01.hyp.15.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Deuterium oxide normalizes blood pressure and vascular calcium uptake in Dahl salt-sensitive hypertensive rats.

Abstract: This study examined the effect of 25% deuterium oxide in drinking water on systolic blood pressure, uptakes of calcium, and rubidium 86 by aortas of Dahl salt-sensitive rats on 0.4% (low) and 8% (high) sodium chloride (salt) diet. Twenty-four rats were divided into four groups. Groups I and II were on the low salt diet and groups HI and IV on the high salt diet from 6 weeks of age. Additionally, at 10 weeks of age groups I and III were placed on 100% water and groups II and IV on 25% deuterium oxide. At 14 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…These in vitro effects of D 2 0 were concentration dependent. 27 ' 28 In experiments using guinea pig ventricular myocytes, others have reported that isotopic substitution of deuterium for hydrogen may affect cell surface Ca 2+ channels. 25 The antihypertensive effects of D 2 O may be the result of increased blockage of calcium channels by bound deuterium ions.…”
Section: Kcl-induced High Camentioning
confidence: 99%
See 1 more Smart Citation
“…These in vitro effects of D 2 0 were concentration dependent. 27 ' 28 In experiments using guinea pig ventricular myocytes, others have reported that isotopic substitution of deuterium for hydrogen may affect cell surface Ca 2+ channels. 25 The antihypertensive effects of D 2 O may be the result of increased blockage of calcium channels by bound deuterium ions.…”
Section: Kcl-induced High Camentioning
confidence: 99%
“…- 28 The objectives of the present study were to investigate the dose-dependent effect of 5%, 10%, and 20% D 2 O in drinking water on …”
mentioning
confidence: 99%
“…Calcium uptake by thoracic aortic tissues was measured as described previously, 20 - 21 and thoracic aortas were excised and dissected free of connective tissue in a constantly oxygenated HEPES buffer (pH 7.4) solution containing: 150 mM NaCl, 4.5 mM KC1, 10 mM D-glucose, 5 mM HEPES, 1.5 mM CaCl 2 , and 1 mM MgCl 2 . Aortas were then cut into 2-3-mm long segments.…”
Section: Measurement Of Calcium Uptake By Thoracic Aortasmentioning
confidence: 99%
“…Under these conditions, efflux of intracellular calcium is prevented and only the extracellular calcium is effectively washed away. 20 The tissues were then blotted, wet weights were measured and transferred to counting vials containing 100 fil H 2 O and 1 ml Protosol (New England Nuclear, Boston, Massachusetts, USA), and then were placed in a water bath for 2 hours at 60°-70°C. After digestion, 100 y\ glacial acetic acid was added to each vial followed by 10 ml liquid scintillation fluid (BDH Chemicals, Toronto, Canada), and the solution was counted in a Beckman liquid scintillation counter (Beckman Instruments, Fullerton, Calif. 86 Rb + uptake in vitro in thoracic aortic rings by an essentially similar method as described previously.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation